A qualitative and quantitative determination of the amino acids and aroma substances, especially esters, aldehydes and ketones in musts and wines - Venter, P. J. (Peter Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (DScAgric)--Stellenbosch University, 1958.